Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai SMP Negeri 2 Muara Pinang Kabupaten Empat Lawang - Yadi Maryadi; Yulia Misrania (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine whether there is an influence of the work environment on employee performance and to determine how influential it is on employee performance. This research uses associative research with a quantitative approach. There are two variables used in this study, namely the work environment (X) and employee performance (Y). Data collection was obtained by distributing questionnaires directly to employees of SMP Negeri 2 Muara Pinang, Empat Lawang Regency. The sample used in this study were 55 respondents. From the results of the simple linear regression analysis test, it shows that there is a positive and significant influence between the work environment variable and the employee performance variable. So it can be concluded that the work environment has a positive and significant influence on employee performance by 2.46% with the equation Y = 23,148 + 0.246. This means that Ho is rejected and Ha is accepted, which means that there is an influence of the work environment on employee performance at SMP Negeri 2 Muara Pinang, Empat Lawang Regency. Which can be seen from the results of the t test where the significant value is 0.000, which means it is smaller than 0.05 so that the hypothesis is accepted.